Structural Quality in Waterfront Green Space of Shaoyang City by Scenic Beauty Evaluation - Yang, Xianjun (Asian Journal of Chemistry, 2014)
Quality of landscape structure in green space of built-up waterfront areas in Shaoyang City were quantitatively assessed on the bases of scenic beauty estimation (SBE) in this paper. Scenic beauty estimation modals were constructed by using polybasic mathematical theory I. The results showed the main factors influencing the quality of forest landscape were green space ratio, canopy coverage, quantity of plant colour, contrast of the colour, composition of plant growth forms and wild-like degree of landscape. The main factors affecting the structure of green space around artificial landscape buildings, building pieces and roads in the county parks were relative trunk height below crow, harmony of landscape, planting pattern of tree, branch and leaf density of trees and style of building. The main factors determining the quality of waterfront landscape more efficiently were space occupied by vegetation, harmony of landscape, planting pattern of trees and vertical stratum structure of vegetation.